A high-sensitivity, high-throughput newborn screening assay for congenital cytomegalovirus—is it time for universal screening in the United Kingdom? - Payne, H.; Aaltoranta, M.; Veikkolainen, V.; Kent, N.; Gkouleli, T.; Lennon, A.; Ramgoolam, T.; Adams, S. P. (Frontiers in Pediatrics, 2025)
IntroductionCongenital cytomegalovirus (cCMV) is the leading cause of neurodevelopmental and hearing impairment resulting from in utero infection, affecting over a million infants globally each year. Early antiviral treatment can limit sequelae; however, most newborns are diagnosed late—or not at all—due to the lack of universal screening. Ensuring the availability of appropriate screening tools is critical to facilitate accurate and timely cCMV diagnosis.MethodsA high-sensitivity, high-throughput commercial CMV PCR kit targeting the RRP30 control gene and a conserved region of CMV DNA was provided by Revvity and tested in three population groups: (1) leftover dried blood spot (DBS) samples from the UK newborn screening programme, (2) DBS samples from children with CMV viraemia unrelated to cCMV, and (3) DBS and dried saliva samples from infants with and without cCMV.ResultsOf 3,345 anonymised newborn DBS samples analysed, CMV was detected in 22 cases (0.66%), with a mean cycle threshold value of 36.70 (range 31.87–41.68). Assay development demonstrated a sensitivity of 2.04 CMV IU per reaction. This level of sensitivity was replicated using DBS samples prepared from infant/child blood samples with known levels of CMV, suggesting that the sensitivity reflects 2,000–3,000 CMV IU/mL blood.DiscussionWe demonstrated high analytical sensitivity of the qPCR assay with an optimal extraction protocol, making it an effective strategy for cCMV screening using DBS samples. These data suggest a potential cCMV incidence rate of up to 0.66% in the United Kingdom, equivalent to 3,960 infants per year, 25% of whom may develop long-term sequelae, which could be improved through early diagnosis and treatment.